Better non-invasive endoscopic procedure: endoscopic ultrasound or magnetic resonance cholangiopancreatography? - Rusmir Mesihović; Amila Mehmedović (Medicinski glasnik, 2018)
Aim: To present our experience with a diagnostic ability of endoscopic ultrasound (EUS) and magnetic retrograde cholangiopancreatography (MRCP) in cases of choledocholithiasis verified by endoscopic retrograde cholangiopancreatography (ERCP). Methods: This retrospective study was conducted after a collection of data involving 58 suspected choledocholithiasis patients who underwent ERCP from January 2013 to December 2015. Patients who were diagnosed with choledocholithiasis on the basis of clinical symptoms and radiological findings and who underwent ERCP were included in this study. The first group (29 patients) underwent EUS, and the second group (29 patients) underwent MRCP. The ERCP was performed in both groups. Sensitivity, specificity and diagnostic accuracy of EUS and MRCP were determined by comparing them with ERCP, which was considered to be a gold standard. Results: Gender representation was in favour of males, 58:42%. The mean age was 55.5 years. In the group 1 (EUS) 22 patients were found to have choledocholithiasis using ERCP. The EUS stone detection rate was 88%. Endoscopic ultrasound showed sensitivity (97%), specificity (67%) and accuracy (88%), positive predictive value (PPV) of 88%, negative predictive value (NPV) of 80%. In the group 2 (MRCP) 16 patients were found to have choledocholithiasis by ERCP. MRCP sensitivity was 81%, specificity 40%, PPV of 74%, NPV of 50%. Conclusion: The EUS was a superior non-invasive tool in comparison with MRCP for detecting choledocholithiasis, which was confirmed using ERCP.
Keywords: choledocholithiasis; cholangiopancreatographies; endoscopic ultrasonography; magnetic resonance